EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS PROYEK PADA MATERI SISTEM KOORDINASI MANUSIA DI SMPN 1 TERBUKA BOJONGGEDE - Risalati Maulina Ulya; Dyah Aniza Kismiati (Universitas Tribhuwana Tunggadewi, 2025)
The coordination system is the control center of our body. This study aims to determine the improvement of learning outcomes of grade IX students in the human coordination system material at SMPN 1 Terbuka Bojonggede after the implementation of the Project-Based Learning (PjBL) model. The method used in this study is Classroom Action Research (PTK) with data collection techniques in the form of observation and written tests, pre-tests and postes. The results of the study show that by applying the Project-Based Learning (PjBL) model, it can improve students' learning outcomes and understanding of abstract concepts such as neural structure and physiological processes in the human coordination system. This is proven in the first cycle, only 72% of grade IX students of SMPN 1 Terbuka Bojonggede achieved learning completion. Meanwhile, in the second cycle, the completeness of student learning managed to increase to 100%. The project-based learning model is a model that is based on the real life of students. This model is able to improve thinking skills and improve skills and knowledge so that the application of the project-based learning model can optimize student learning outcomes.